Think agile how smart entrepreneurs adapt in order to succeed - Williams, Taffy (AMACOM, American Management Association, 2015)
When entrepreneurs lock themselves into one strategy, one product, one distribution method-and one way of thinking about their business-they limit their potential, and lower their chances of capitalizing on economic, industry, or market changes. Instead, those determined to keep up with today's constantly changing business environment need to master a new mindset: agility. Think Agile helps entrepreneurs assess their level of flexibility-and learn to be open-minded and option-oriented when it comes to sources of funding; launch timetables; planning; repurposing everything from products to peop.
Includes index. - Includes bibliographical references and index. - Print version record
Keywords: Entrepreneurship; Organizational change; Organizational effectiveness; Entrepreneuriat; Changement organisationnel; Efficacité organisationnelle; entrepreneurs; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior